2014
DOI: 10.1016/j.ymgmr.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in PKU: The results from 8 centres in Europe and Turkey

Abstract: IntroductionIn PKU there is little data comparing the prevalence of overweight and obesity in different countries. The aim of this cross sectional study was to evaluate prevalence data from different PKU treatment centres in Europe and Turkey.Subjects and methodsIn children, body mass index (BMI) and z scores and in adults BMI were calculated in 947 patients (783 children aged < 19 years; 164 adults aged ≥ 19 years) with PKU from centres in Europe and Turkey (Ankara, Birmingham, Brussels, Copenhagen, Groningen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 9 publications
1
33
1
Order By: Relevance
“…Furthermore, the BMI of parents was not recorded and it is acknowledged that this may have influenced eating habits. However, previous study in this group of PKU children has indicated that the incidence of obesity is no different than in the general population [8] .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the BMI of parents was not recorded and it is acknowledged that this may have influenced eating habits. However, previous study in this group of PKU children has indicated that the incidence of obesity is no different than in the general population [8] .…”
Section: Discussionmentioning
confidence: 53%
“…It is well established that low Phe diets are high in carbohydrate (59–67% of energy) but lower in fat (23–26%) [1] , [2] , [3] , [4] , [5] than the general populations diet (50–52% carbohydrate and 33% fat) [6] . Eating behaviours evolve in the early years of development, and in PKU, a high carbohydrate diet may influence taste preferences and eating behaviour, potentially influencing the development of obesity in later life [1] , [7] , [8] , [9] . Parents help mould children's early experiences with food, providing both the genes and the environment for children [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies consider that individuals with PKU are more vulnerable to weight increase, 11,30,31 especially females. 25.27,32 According to data published by Gokmen Ozel et al, 32 the prevalence of being overweight and obese in the general female population can range from 17 to 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Many adults with PKU have a vegan-like diet but may not take Phe-free L-amino acid supplements [ 74 ] and consequently may be at risk of micronutrient deficiencies [ 75 ]. There is increasing reports of females (and not males) with PKU being overweight and obese [ 76 , 77 ]. The risk of comorbidities makes dietary management more complex [ 78 ].…”
Section: Initiation Of Treatment and Treatment For Lifementioning
confidence: 99%